Acantholytic squamous cell carcinoma of oral cavity, mimicker of angiosarcoma: A rare case report - Bothale, Kalpana; Mahore, Sadhana; Maimoon, Sabiha; Bothale, Akanksha (Indian Journal of Case Reports, 2018)
Acantholytic squamous cell carcinoma (ASCC) is an uncommon variant of SCC. It was first described by Lever in 1947. It usually develops on sun-exposed areas of older-aged individuals. Histologically, the tumor consists of a nodular, epidermal-derived proliferation that forms islands like structures. At least focally or sometimes extensively, the tumor cells show a loss of cell cohesion within the central gland-like or tubular spaces. The lesions present as slowly growing scaly and occasionally ulcerated papules or plaques. Areas of acantholysis may produce large intraepidermal cavities which may extend to the adjacent follicular structures. ASCC is rarely seen in the oral cavity. Here, we report an unusual case of ASCC of the oral cavity, which was initially misinterpreted as angiosarcoma on histopathology. Then, on immunohistochemistry, ASCC was confirmed.